Venetian istorie: re-evaluating Giovanni Mansueti's narrative painting (1500-30's) - Matino, Gabriele (2014)
This thesis challenges existing studies on Giovanni Mansueti (active 1485-1526/27) that have generally tended to undervalue his contribution to Venetian narrative painting. Rather, drawing on extensive primary research my work demonstrates how Mansueti was one of the major interpreters of the “eyewitness style”, in fact a master able to picture the unique requirements and expectations of his various patrons.